PENGARUH PEMBERIAN EKSTRAK BAYAM MERAH TERHADAP PENINGKATAN KADAR HB PADA IBU HAMIL DI KLINIK VINA MEDAN: PENGARUH PEMBERIAN EKSTRAK BAYAM MERAH TERHADAP PENINGKATAN KADAR HB PADA IBU HAMIL DI KLINIK VINA MEDAN - Adriana Bangun (Jurnal Maternitas Kebidanan, 2021)
Nutritional anemia is a condition with a blood hemoglobin level that is lower than normal as a result of the inability of the tissues that make up red blood cells in their production to maintain hemoglobin levels at the national level. Red spinach is often found in traditional markets in the city of Medan. However, there are still many pregnant women who do not know that red spinach can increase HB levels in pregnant women, so that so far red spinach is still used by pregnant women for vegetables only. This study aims to help pregnant women obtain food sources that are rich in iron and very easy to obtain in their environment. So that there are no more pregnant women who experience anemia, so that it can reduce maternal mortality through bleeding during childbirth. The design of this study used a Quasi Experiment One Group Pre Post Test. Namely by looking at the increase in maternal HB levels before and after consuming red spinach extract. Sampling was done by total sampling technique, namely as many as 30 pregnant women. Analysis with independent t test statistical test with a confidence level of 95%. The results showed that the average hemoglobin level before giving the red spinach extract was 21.22 g / dL (minimum = 9.0 g / dL and maximum = 10.2 g / dL), the average hemoglobin level after giving spinach extract. red is 41.12 g / dL (minimum = 10.0 g / dL and maximum = 11.7 g / dL), the difference in hemoglobin levels before and after giving red spinach extract has increased hemoglobin levels by 27 people (89.12% ) and there is an effect of giving red spinach extract on increasing hemoglobin levels in pregnant women at the Vina Clinic Medan.